The Selli level of the Gargano Promontory, Apulia, southern Italy: foraminiferal and calcareous nannofossil data. - COBIANCHI, MIRIAM; LUCIANI V; MENEGATTI A. (Elsevier Science Limited:Oxford Fulfillment Center, PO Box 800, Kidlington Oxford OX5 1DX United Kingdom:011 44 1865 843000, 011 44 1865 843699, EMAIL: asianfo@elsevier.com, tcb@elsevier.co.UK, INTERNET: http://www.elsevier.com, http://www.elsevier.com/locate/shpsa/, Fax: 011 44 1865 843010, 1999)
Two Aptian pelagic stratigraphic sections from the northern Gargano Promontory, Apulia, southern Italy, were investigated on the basis of foraminifera and calcareous nannofossils. The successions are characterized by cyclically arranged marls and marly/cherty limestones and can be referred to the Scisti a Fucoidi Formation. In the lower portion of this unit a thin black shale segment was recognized. Planktonic foraminiferal and calcareous nannofossil biostratigraphic data enable the level to be attributed to the upper part of the Globigerinelloides blowi and Chiastozygus litterarius Zones of late Early Aptian age. These data suggest that the black shale is equivalent to the Selli Level of the Umbria-Marche Basin, which is considered to be the sedimentary expression of the global oceanic anoxic event OAE 1a. A perturbation of the biotic signal occurs across the Selli Level. A crisis of Globigerinelloidids and nannoconids precedes and follows the anoxic episode, and a marked increase in the eutrophic indicators (hedbergellids, Zygodiscus erectus, Biscutum constans, radiolaria) was observed. These critical conditions associated to the OAE1a are widely documented and generally related to a high fertility episode of surface water. However, with respect to the Gorgo a Cerbara section (Umbria-Marche Basin), the Selli Level from the Gargano is not completely barren of calcareous plankton, probably suggesting slightly less fertile conditions in the surface water or a shallower environment. Moreover, the occurrence of the benthonic genus Spirillina indicates local dysaerobic conditions versus complete anoxia on the sea floor.